Points of Entanglement in French Caribbean Travel Writing (1620-1722) - Kullberg, Christina (Springer Nature, 2023)
This open-access book investigates Francophone Caribbean literature by exploring and analyzing French seventeenth-century travel writings. The book argues for a literary re-examination of the representation of the early colonial Caribbean by proposing theoretical linkages to contemporary Caribbean theories of creolization and archipelagic thinking. Using Édouard Glissant’s notion of points of entanglement, Christina Kullberg claims that the historical, social, and political messiness of the Caribbean seventeenth century make for complex representations and expressions, generating textual instability despite the travelers’ apparent desires to domesticate the islands. Taking a synoptic approach to travel narratives in French from 1620 up to the publication of Labat’s Nouveau voyage aux Isles de l’Amérique in 1722, Kullberg examines textual instances where the islands and the peoples of this period disrupt and unsettle dominant French narratives and enter productively into the construction of knowledge and the representations of the region. Kullberg’s contribution is to read French early modern travels in situ as shaped by the archipelagic geography, its history and social formations in order to interrogate both the construction and the limitations of discourses of power.